Allogeneic Liver Transplantation in Nonhuman Primates: Surgical Technique With Stable Postoperative Outcomes - Katsuhiro Tomofuji, MD, PhD; Daniel J. Cloonan, MD; Taylor M. Coe, MD; Olivia Bourgeois, BS; Rudy Matheson, BS; Ahmad Karadagi, MD, PhD; Anil Kharga, MBBS; Toshihide Tomosugi, MD, PhD; James F. Markmann, MD, PhD; Shoko Kimura, MD, PhD (Transplantation Direct, 2025)
Background. Nonhuman primate models are essential in preclinical transplantation studies. Although many advances in medical and surgical therapies have been achieved in liver transplantation research using rodent models, nonhuman primate models have not been widely used because of their technical complexity. As scientific inquiries into tolerance-free and ischemia-free models of transplantation continue to progress, it is vital to establish a standard nonhuman primate model. We attempted to establish a feasible and stable nonhuman primate model for orthotopic liver transplantation using baboons. Methods. Orthotopic allogeneic liver transplantations were performed in 3 cynomolgus macaques and 5 baboons. Portocaval shunts and extracorporeal bypasses were performed as previously described for cynomolgus macaques. In baboon models, minimization of the anhepatic time was attempted without the bypass technique. Survival, postoperative clinical course, histopathology, and liver enzyme levels were assessed. Results. The first 2 macaques were euthanized because of gastric necrosis and pneumonia. The third had bypass failure of circulation and developed coagulopathy, which occurred at the end of the study during surgery. In baboons, all 5 recipients survived for >2 mo. The first 3 recipients, whose bile ducts were reconstructed with choledocholedochostomy (duct-to-duct), showed elevated liver function and bile duct enzymes. Therefore, choledochojejunostomy was performed in the other 2 cases, revealing normal liver function postoperatively. Conclusions. We report successful and consistently stable outcomes of nonhuman primate liver transplantation in baboons. In addition to existing cynomolgus macaque models, our method offers a promising approach and contributes to further clinical adaptation of translational studies.